Complete resolution of endometriotic cyst with letrazole and meprate treatment - Khazi, A. A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Pelvic endometriosis is seen in 5% gynecological patients it leads to infertility. Various treatment options are available like oral contraceptives and progesterones. Letrazole is an aromatase inhibitor which decreases estrogen level in endometriotic cyst wall. Here, is reported pelvic endometriosis successfully treated with letrazole and meprate.